Faktor-Faktor yang Mempengaruhi Permintaan Pisang Barangan di Kota Medan - Yudha Filistea Purba; Yusniar Lubis; Faoeza Hafiz Saragih (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
Barangan Banana is a commodity that is already popular in the community has very important economic and social value, the need for bananas continues to increase in line with the population and income level of the community. This study aims to determine what factors influence the demand for barangan bananas in Medan, in the Market Petisah kecamatan medan petisah North Sumatra province from Demand, Price, Number of Family Members up to Consumers income and Method used incidental sampling is a technique that is required when sampling, samples taken as many as 30 consumers who buy barangan bananas in petisah market separating Medan petisah , and the data collected are primary and secondary data, the analytical method used is multiple linear regression test with software tools namely SPSS 21, the highest price of barangan banana 18,000, the price of other bananas (Ambon) the highest 15,000, the number of family members inggi 6, the highest income of 5,000,000.The results of this study concluded that the factors that influence the demand for barangan bananas in medan city, the separating market in medan petisah sub-district. Simultaneously influential are the prices of barangan bananas, Ambon banana prices, family members, and consumer income significantly, this can be seen from t count 4.027 is greater than t-table 1.708.